Spermatogonial stem cells protein marker identification from in-vitro differentiation of Non-Obstructive Azoospermia (NOA) testes biopsies cells: an approach in line with Maqasid al Shariah to maintain the heredity - Abdul Wahab, Azantee Yazmie; Md Isa, Muhammad Lokman; Ramli, Roszaman; Mat Yusof, Afzan (2016)
Azoospermia is present in 15% of infertile cases and it is a major concern due to inability to produce sperm. Most of IVF (in-vitro fertilization) clinics in abroad had been using sperm donation via sperm bank facilities as a solution for infertile couple to have their own offspring. In Islam, it is forbidden to use sample from male other than their spouse. It is according to maqasid syari’ah to ensure the heridity of the human being. Based on the latest technology, one approach of stem cell differentiation process had been established to produce mature cells from primitive or immature cells (stem cells). This technology is in line with the concept of maqasid syari’ah since we are using the cells from one person. Therefore, we try to adopt this technology to study a potential of testicular cells from non-obstructive azoospermic (NOA) patient to undergo in vitro spermatogenesis. Samples were cultured in modified human embryonic stem cells (HESC) media with specific growth factors; basic fibroblast growth factor (bFGF)and leukemia inhibitory factor (LIF). Protein expressions were analyzed by immunofluorescent staining on day 49 and 90 of culture. Results shown spermatogonial stem cells (SSCs) colonies formed after 14 to 21 days then the cells were successful expanding and stable in duration of 49 days. Then SSCs were differentiated into later stage of spermatogenesis on day 90. Four specifics SSCs protein markers were identified on day 49; ITGA1, ITGB1, CD9 and GFRA1 whereas SCP3 and TP1 proteins were expressed on day 90. This in vitro spermatogenesis suggested a closer approach for future clinical purposes for Muslim NOA patients in order to have their own children.